DESIGN OF MANIPULATOR ROBOT IN UNMANNED GRENADE TAMER (UGT) - Ayip Rivai Prabowo; Endro Prasetijoadi; Dueng Deriva; Wawan Kusdiana (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Low safety factor in the Standard Operating Procedure (SOP) in handling grenades that fail to explode at the training location can be fatal for personnel and instructors. In a previous study, a stick manipulator was designed. However, this tool has disadvantages because the operator is too close to explosives. By considering the security of personnel, the authors make